Clifford Codes - Klappenecker, Andreas; Roetteler, Martin (R. Brylinski and G. Chen, editors, The Mathematics of Quantum Computation. CRC Press, 2002., 2002)
Quantum error control codes allow to detect and correct errors that are due to decoherence effects. We review some basic properties of these codes and give some constructions. Our main focus will be on a construction of quantum error control codes that have been introduced by Knill in 1996 with the intention to generalize stabilizer codes. These so-called Clifford codes can be constructed and analyzed with tools from representation theory of finite groups. We show that a large class of Clifford codes are actually stabilizer codes. And we construct the smallest example of a Clifford code that is not a stabilizer code.